Compartmentalization of Animals: Toward an Understanding of How We Create Cognitive Distinctions between Animals and Their Implications. Issue 1 (14th May 2019) - Amiot, Catherine E.; Lépine, Olivier; Zaky, Julie
Abstract: The nature of our relationships with nonhuman animals is complex and varies greatly across different types and species of animals. The goal of the current research is to investigate the differences that exist in our perceptions of animals based on their type, specifically by focusing on the phenomenon of compartmentalization. Two studies investigated the compartmentalization of farm animals relative to other types of animals (e.g., pets, wild animals). In Study 1, a greater tendency to compartmentalize farm animals correlated negatively with the attribution of a higher status to these animals, with more differentiated perceptions between the standing of farm animals and pets, and with a lower inclusion of animals in the self. In Study 2, different justifying beliefs taping into human superiority, the endorsement of carnism, and feeling threatened by vegetarianism mediated the negative relation between compartmentalization of farm animals and the negative emotional outcomes felt when eating meat. Together, these findings confirm the relevance of applying the notion of compartmentalization to the specific realm of human–animal relations.